Exploring the impact of housing routine on lying behavior in horses measured with triaxial accelerometer - Gobbo, Elena; Maccario, Chiara; Zupan Šemrov, Manja; Bovo, Marco; Atallah, Elie; Minero, Michela; Dalla Costa, Emanuela (Frontiers in Veterinary Science, 2025)
IntroductionMethods to assess the positive behavior of horses in relation to their environment can be used to provide information to enhance animal welfare. One of the most important experiences that can be observed in mammals is sleep, a universal behavior relevant for the welfare of all species. To achieve paradoxical sleep, horses must lie down in lateral recumbency for a sufficient time, but they only do so when feeling safe and comfortable. Recently, technological tools like accelerometers have opened the possibility of non-invasive continuous monitoring of lying behavior, thus implementing the way we assess equine behavior in relation to their management and environment.MethodsThe aim of this study was to investigate whether a sudden change in housing routine affects lying behavior in horses. In 10 riding school horses, lying behavior was continuously monitored using triaxial accelerometers for two separate 5-day periods, each under a different housing routine (i.e., ordinary: in a paddock in small groups; modified: in single boxes).ResultsThe results show no statistical differences in the total daily duration of lying behavior between ordinary (25.19 ± 21.81 min) and modified (23.16 ± 20.05 min) housing routines. However, in the ordinary housing routine, when horses were kept outdoors in groups of varying sizes, larger groups exhibited synchronized lying behavior, with longer lying bouts, while smaller groups lay down more frequently throughout the day.DiscussionThe results show that sudden change in housing routine does not have a significant effect on lying behavior, while group size appears to be an important factor for behavioral synchronization. However, the small sample size, the single location, and mixed-age and sex population may have influenced the findings. Accelerometers were shown to be beneficial for monitoring natural behaviors such as lying and thus inferring information about equine behavior in relation to daily routine management.